2007
DOI: 10.1002/asi.20698
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge sharing in online environments: A qualitative case study

Abstract: This study expands the perspective of knowledge sharing by categorizing the different types of knowledge that individuals shared with one another and examining the patterns of motivators and barriers of knowledge sharing across three online environments pertaining to the following professional practices-advanced nursing practice, Web development, and literacy education. The patterns indicate the different possible combinations of motivators or barriers that may exist in individuals. Data were gathered through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 38 publications
5
93
0
1
Order By: Relevance
“…One possible reason is that knowledge exchange through a visible computer-mediate system is promoted by generalized reciprocity (Wasko and Faraj 2005). This finding is consistent with Hew and Hara's (2007) research, in which they found reciprocity to be a reason for members' contributions in online environments.…”
Section: Perceived Benefitssupporting
confidence: 85%
“…One possible reason is that knowledge exchange through a visible computer-mediate system is promoted by generalized reciprocity (Wasko and Faraj 2005). This finding is consistent with Hew and Hara's (2007) research, in which they found reciprocity to be a reason for members' contributions in online environments.…”
Section: Perceived Benefitssupporting
confidence: 85%
“…We have found a great deal of common ground with research on social learning and Web 2.0. For example, the importance of performance criteria and being able to select people based in similarity within mentoring [2], is mirrored by the need to see and know about others online [13] before developing connections and trust [3]. In this model of mentoring (closer to peer mentoring or peer support in workbased learning) the relationships are likely to be more diffuse and feature connections that vary in frequency and intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty out of Bartol and Srivastava [24] participants indicated that they are intended to share knowledge because of a sense of responsibility. The finding discrepancy may come from the different methodology designs as the first two studies are designed empirical experiment while the data from Hew and Hara [17] is conducted from observation and interviews. Future research studies should draw attention to investigate the motivational effects of reciprocity, especially the generalized reciprocity, on knowledge sharing behavior.…”
Section: Organizational Factors 1) Incentive Mechanismmentioning
confidence: 99%
“…For instance, researchers have been investigating what factors motivate successful knowledge sharing [1], [9], [11], [13]- [21] and what factors hinder knowledge sharing among individuals [1], [11], [12], [17]. Although these studies provide useful insights into the factors that significantly affect the behavior of knowledge sharing, there are some discrepancies of findings among the different studies.…”
Section: Introductionmentioning
confidence: 99%